The Effect of Autochthonous Starter Culture, Sugars and Temperature on the Fermentation of Slavonian Kulen - Krešimir Mastanjević; Dragan Kovačević; Jadranka Frece; Ksenĳa Markov; Jelka Pleadin (Food Technology and Biotechnology, 2017)
In this study, the effect of an isolated and well-characterised autochthonous starter culture, glucose and maltodextrin (w=0.8 %) and temperatures of 12 and 20 °C on fermentation and quality of Slavonian kulen produced using the traditional technology and recipe were investigated. Physicochemical and microbiological analyses were carried out after 20 days of fermentation. Upon the completion of the production process (90 days), a sensory analysis was carried out. Furthermore, pH value was continuously measured throughout the twenty-day fermentation period. The addition of an autochthonous starter culture and sugars and diff erent fermentation temperatures significantly (p<0.05) affected the instrumental colour and texture parameters of the Slavonian kulen. The fermentation was most intense in the samples with added autochthonous starter culture and 0.8 % glucose, and fermented at 20 °C. Microbiological analysis showed that samples with added autochthonous starter culture and fermented at higher temperature contained a higher number of lactic acid bacteria and coagulase-negative staphylococci and were safe. Sensory evaluation confirmed the outcomes of physicochemical and microbiological analyses and showed differences among samples fermented at two different temperatures and with added glucose or maltodextrin and an autochthonous starter culture.